CCNA 200-301 Exam Prep - Odom, Wendell (Pearson IT Certification, 2020)
15+ Hours of Video Instruction Overview CCNA 200-301 Exam Prep LiveLessons gives you the edge you need to pass the Cisco CCNA exam. Wendell Odom, best-selling author of the CCNA 200-301 Official Cert Guides, provides more than 15 hours of video training detailing what to expect on the CCNA 200-301 exam. This is an essential course for anyone interested in passing the CCNA exam. CCNA 200-301 Exam Prep LiveLessons provides more than 15 hours of video training detailing common exam traps, pitfalls, and difficulties on the Cisco CCNA exam. Features include background information on the exams, a deep dive into common mistakes and misunderstandings certification candidates make when taking the exams, and exam walkthroughs with sample questions so you can see firsthand the types of questions you'll encounter in the testing facility. In Module 1, best-selling author and expert instructor Wendell Odom explores essential information about the Cisco CCNA certification, such as what to do if you get stuck on a question, what to expect in the testing facility, and how to manage your time. Module 2 is dedicated to helping you preemptively learn about common misunderstandings people make about the exams in all six exam domains: network fundamentals, network access, IP connectivity, IP services, security fundamentals, and automation and programmability. This section also focuses on commonplace mistakes that people make. Module 3 takes you on a deep dive into the types of questions you'll encounter for each domain in the exam. In this section, you will have the opportunity to assess sample questions and see firsthand how the author solves each one while detailing why the right answer is correct and how to avoid pitfalls. This course is meant to help you prepare for your exam and identify areas of weakness, while improving your conceptual knowledge and hands-on skills. About the Instructor Wendell Odom, CCIE No. 1624, creates many of the best-selling Cisco certification products of their types, particularly in the routing and switching space. He has pioneered the authorized Cisco Cert Guide series at Cisco Press and has written every edition of the leading CCENT and CCNA Cert Guides. He has written more than 30 editions of networking books, video, and software products, ranging in depth from the introductory level to CCIE. Wendell has worked as an instructor, course developer, network engineer, and consultant. Find links to more study tools and resources (including.